Optimization of Citric acid production from Locally isolate fungus Aspergillus niger by solid state fermentation - Mohi-Aldin, Mohammed O.; Hussain, Aiden M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study aimed to obtain an isolate of a mold that has well characteristic for production of citric acid from raw materials available locally by solid-state fermentation and determination of the optimum conditions for production .Fourteen mold isolates producing acid were obtained from different sources, involved decayed fruits and soils. These isolates were subjected to initial qualitative screening followed by secondary quantitative screening In secondary screening a method combined between the submerged fermentation and solid-state fermentation was followed using a piece of sponge saturated by nutrients required for growth and production of acid. It was found that the isolate of A7 was the highest producer for citric acid than any other isolates including three standard isolates obtained from the Laboratory of Biotechnology/ College of Agriculture. Morphological analysis under the light microscope and cultural characteristics on solid media showed that the isolate A7 belongs to Aspergillus niger. Different raw materials were used for the production of citric acid from this isolate by solid-state fermentation included sunflower waste, wheat bran, rice bran as well as ground corn. It  was found that the latter was better than others,therefore  it was used for optimization of production conditions of the acid. The optimum conditions were achieved on ground corn moistened with water at a ratio 1:0.75 with an initial pH 3 inoculated with 107 spores/ml during an incubation time of 3 days at 25 C0..The productivity of   citric acid under these conditions was 20.8 gm/100 gm of the media. Supporting the media with 1% of yeast extract and adding 3% of methanol to moisten solution was found to increase the productivity to 23.0 g /100 g, while the effect of ethanol was limited. Citric acid produced in this study was detected quantitatively and qualitatively by High Performance Liquid Chromatography (HPLC) and it was found that the amount of citric acid produced after three days of incubation under optimum production conditions was Ù¡Ù£Ù«Ù¥Ù¤ gm/ 100 gm of media. This value was less than that estimated by the chemical method using pyridine. It was also noted that, beside citric acid, there was another compound produced in visible quantity. Although this compound was not recognized in this study, it is thought to be any of organic acids of Kreb's cycle and this compound may be interact with citric acid when determined by pyridine. According to results of determination of citric acid by HPLC it can be said that the actual production of citric acid was as mentioned above (13.54 gm/ 100 gm) but not as estimated by the chemical method using pyridine